DEVELOPING MODULE OF CHILDREN LITERATURE TO INCREASE THE STUDENTS' CRITICAL THINKING - Hajarudin Al Fikri; Enny Zubaidah (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract:This study aimed to (1) produce a module of children literature based on nationalism character to improve the critical thinking ability of the fourth grade students of MIN Boyolali, and (2) measure the effectiveness of the module used in classroom toward critical thinking ability of the fourth grade students of MIN Boyolali. Set within the research and development type, this study adapted the development procedure formulated by Borg and Gall (1983). Data were collected through interview and observation, product validation, questionnaire of the teacher and the students’ response, and the result of pre-test and post-test which was analyzed using independent sample t-test. Meanwhile, the effectiveness was tested through quasi experiment. The result of the research showed that the module was categorized as “fit” by material and language expert; while the media expert categorized it as